2007
DOI: 10.1007/s10741-007-9007-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy induced by sustained β-adrenoreceptor activation: pathophysiological aspects

Abstract: Cardiac hypertrophy is promoted by adrenergic over-activation and represents an independent risk factor for cardiovascular morbidity and mortality. The basic knowledge about mechanisms by which sustained adrenergic activation promotes myocardial growth, as well as understanding how structural changes in hypertrophied myocardium could affect myocardial function has been acquired from studies using an animal model of chronic systemic beta-adrenoreceptor agonist administration. Sustained beta-adrenoreceptor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
1
27

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 236 publications
(300 reference statements)
6
113
1
27
Order By: Relevance
“…It is worth noting that this mechanism functions without an overall chronic activation of ␤-adrenergic pathways, that has proven detrimental to cardiac function (see Ref. 41 for review). Thus the cTnI N-terminal extension serves as a mechanism to modulate cardiac Ca 2ϩ sensitivity and cross-bridge cycling by ␤-adrenergic induced phosphorylation at Ser-23/24 or through its removal, both resulting from an alteration of its interaction with TnC to favor the closed conformation.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that this mechanism functions without an overall chronic activation of ␤-adrenergic pathways, that has proven detrimental to cardiac function (see Ref. 41 for review). Thus the cTnI N-terminal extension serves as a mechanism to modulate cardiac Ca 2ϩ sensitivity and cross-bridge cycling by ␤-adrenergic induced phosphorylation at Ser-23/24 or through its removal, both resulting from an alteration of its interaction with TnC to favor the closed conformation.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments, transgenic overexpression of 1-adrenergic receptors in the murine heart causes dilated cardiomyopathy (Engelhardt et al, 1999). We also found that metoprolol, a selective 1-adrenergic antagonist, almost completely prevented cardiac hypertrophy and failure of isoproterenol-treated mice (data not shown), indicating that excessive stimulation of 1-adrenergic receptors is the primary cause of myocardial remodeling in isoproterenol-treated mice (Osadchii, 2007;Xiao et al, 2006).…”
Section: Discussionmentioning
confidence: 62%
“…In heart failure, chronic and excessive -adrenergic receptor stimulation causes remodeling of the myocardium and aggravates cardiac function (Osadchii, 2007;Rockman et al, 2002). This concept is the theoretical basis for the treatment of heart failure with -adrenergic antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Chronic AR stimulation promotes pathological remodeling, leading to hypertrophy and/or heart failure. 2,7,8 b 1 -AR signaling shows strong down-regulation in pathophysiological conditions, whereas a 1 -AR expression does not change. 5 Relative increases in a 1 -AR expression levels raise this receptor subtype to a more important role in the regulation of cardiac function in pathophysiological conditions.…”
mentioning
confidence: 99%